A comparative analysis of men’s team and individual large hill (K-125) ski jumping competitions at the 2014 Winter Olympic Games in Sochi - Salamon, Justyna (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Ski jumping is a winter Olympic sport which made its debut at the 1924 Winter Olympics in Chamonix. At the same time the International Ski Federation (FIS) was established. The first large hill ski jumping competition was held during the 1964 Winter Olympics in Innsbruck, and the team ski jumping competition was inaugurated at the Winter Olympics in Calgary in 1988 [1]. Aim of Study. The study is a comparative analysis of team and individual large hill (K-125) ski jumping competitions at the 2014 Winter Olympic Games in Sochi. The analysis covered ski jumpers’ distances, speed, age, nationality, and body build types. Material and Methods. The study sample consisted of all male ski jumpers taking part in the 2nd round of the Olympic competition (30 jumpers in the individual event, 24 in the team event). The ski jumpers’ results, take-off speeds, age and the number of falls were compared using official FIS reports. Results. The characteristics of the individual and team ski-jumping competitions were determined. The ski jumpers’ nationality and age were compared, and a correlation was found between the results and rankings in the competitions and ski jumpers’ body build. Conclusions. High ranks in the ski jumping team competition are not associated with the ranks in the individual competition. The teams usually featured a lower mean age, body surface and greater body mass and body height. The ski jumpers can be categorized as the leptosomic body type
Keywords: Winter Olympics; take-off speed; flight speed; ski jumping; ski training; Rohrer’s index